Analyzing the Effect of Digital Teaching Materials on PAI Students’ Teaching Competence in Microteaching Practice - Andi, Andi Muhammad Iqbal Fallawarukka (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
This study aimed to analyze the effect of students’ ability to design digital teaching materials on their teaching competence in microteaching practice at the Islamic Education Department of Universitas Muhammadiyah Yogyakarta. A descriptive quantitative method with an ex post facto design was applied. A sample of 81 students was selected randomly, and data were collected through a structured questionnaire. Descriptive analysis showed a mean score of 92.547 for digital material design ability and 51.123 for teaching competence. Normality testing confirmed a normal distribution (Sig. = 0.200), and linearity testing indicated a significant linear relationship (F = 72.841; Sig. < 0.01). Simple linear regression revealed a significant influence with B = 0.407; t = 8.188; Sig. < 0.001 and R² = 0.459. These findings indicate that higher digital teaching material design skills are associated with stronger teaching competence. This supports the view that digital competence is a key element in 21st-century education and plays a critical role in shaping future teachers’ professional development through technology-integrated instruction.